Atopias : manifesto for a radical existentialism - Neyrat, Frédéric, 1968- (Lit z., 2018)
Atopias is a manifesto for a radical existentialism that restores the place of the outside that contemporary theory underestimates. Neyrat calls this outside "atopia": not utopia, a dreamt place out of the world, but atopia, the internal outside that is at the core of every being. Atopia is neither an object that an object-oriented ontology might formalize, nor the matter that new materialisms might identify. Atopia is what constitutes the eccentric existence of every being. Etymologically, to exist means "to be outside" and Atopias argues that every entity is outside, thrown in the world without ontological anchor. In this regard, a radicalized existentialism no longer privileges human beings, as Sartre and Heidegger did, but considers existence a universal condition of every being. Now, when our denial of any outside is at its most damaging, is the moment for such a radical existentialism. Only an atopian philosophy-a bizarre, extravagant, heretic philosophy-can rechannel our fear of the outside. Breaking the immanence in which we are trapped, Atopias opens new ways to consider human and animal subjectivity, language, politics, and metaphysics